Corona Virus Disease 2019 (COVID-19) and Its Effect on Renal System, A Systematic Review and Meta-analysis (Iranian Journal of Kidney Diseases, 2020)
Coronavirus disease 2019 (COVID-19) has been recently emerged with various manifestations, mainly on respiratory system. However, other organs might also be involved. Acute kidney injury has been reported as a complication with high variability and controversial results. We aimed to define the frequency of AKI as well as two specific renal biomarkers including BUN and serum Cr among individuals suffering from COVID-19 infection. We investigated Medline/PubMed, Scopus, and Google Scholar databases until 16th April 2020 and included all relevant peer-reviewed published studies without any language limitations. We further categorized patients according to their clinical status into severe, non-severe, and death groups. 18 records on 4528 individuals were assessed. The mean age of individuals were 52.5 ± 24.4 years (males: 55.6%). Prevalence of AKI was 4% (95% CI: 2% to 8%) and was significantly lower among non-severe patients in comparison to deceased ones (1%, 95% CI: 0% to 4%, vs. 31%, 95% CI: 19% to 47%). BUN mean was 5.14 mmol/L (95% CI: 4.60 to 5.69). Non-severe patients had remarkably lower means of BUN compared to deceased or those with severe infection (4.25 mmol/L, 95% Cl: 3.70 to 4.79, vs. 8.9 mmol/L, 95% CI: 7.94 to 9.86, vs. 6.63 mmol/L, 95% Cl: 5.62 to 7.65; respectively). The mean serum Cr was 71.60 mmol/L (95% Cl: 67.56 to 75.64). Our findings suggest that COVID-19 does not seem to involve renal system extensively and other possible mechanisms might be further investigated in this regard.